Sequência didática utilizando protótipo de circuito elétrico de iluminação residencial para o ensino de associação de resistores - Silva, Artur Bezerra da (2020)
The use of experiments for teaching electrical circuits does not normally explore the student's experience, they are practical activities with the intuition of elaborating a resistor association to perform measurements and prove laws, resulting in traditional practices that are reduced to a list of methods previously elaborated without correlating with the individual's daily life. This work aims to propose practical activities for the study of association of lamps in direct current using a prototype of residential floor plan, in order to simulate the connections of the circuit involving electrical panel, conductors, switches and receivers, for the study of association in series, parallel and mixed. We will use a qualitative methodology, exploratory type, in which a case study will be carried out using the product in a high school class and data collection will be carried out based on the analysis of the students' responses to the initial test, final test and the questionnaires inserted in the product. The elaboration and application of the educational product managed to link the theme to the student's daily life, by suggesting a low-cost prototype with the design of a residential floor plan, in order to simulate lamp connections in the single-phase residential electrical circuit. At each meeting, students deepened their knowledge and developed a curiosity in observing the behavior of the brightness of lamps in a residence for each type of association, thus corroborating for potentially meaningful learning.